2001
DOI: 10.1007/s10147-001-8028-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy of carboplatin and gemcitabine against solid tumors: a phase I trial

Abstract: The maximum tolerated doses suggested by this trial are lower than those in other similar phase I trials, but they are consistent with those reported by most of the trials investigating gemcitabine either in combination with cisplatin or in heavily pretreated patients. Carboplatin 4.5 mg/ml per min on day 1 plus gemcitabine 800 mg/m2 on days 1, 8, and 15 every 28 days may represent a promising schedule for further phase II trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Finally, the relationship between side effects and number of courses of chemotherapy also merits discussion. Hematological toxicity is known to increase when gemcitabine is combined with carboplatin rather than with cisplatin 10 -15 • 26 -31 • It represented the dose-limiting toxicity in our prior phase I trial 15 , and in our experience it showed a significant correlation with the number of courses of chemotherapy. In particular, the frequency of grade 3-4 neutropenia was significantly higher in patients receiving more than 4 courses of chemotherapy.…”
Section: Phase II Trialsmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, the relationship between side effects and number of courses of chemotherapy also merits discussion. Hematological toxicity is known to increase when gemcitabine is combined with carboplatin rather than with cisplatin 10 -15 • 26 -31 • It represented the dose-limiting toxicity in our prior phase I trial 15 , and in our experience it showed a significant correlation with the number of courses of chemotherapy. In particular, the frequency of grade 3-4 neutropenia was significantly higher in patients receiving more than 4 courses of chemotherapy.…”
Section: Phase II Trialsmentioning
confidence: 97%
“…However, it is widely accepted that carboplatin should be only preferred to cisplatin when the aim of the treatment is palliation 9 . In the few last years, many phase I trials have investigated different combinations of carboplatin and gemcitabine, and some schedules were proposed for further phase II trials 10 -14 . In a recent phase I trial, we tested a schedule with doses of carboplatin and gemcitabine fairly lower than those used in other similar trials 15 • In the present study, we Acknowledgments: Supported by Istituto Oncologico Romagnolo (IOR). evaluated the activity and safety of this schedule in the palliative treatment of stage IV NSCLC in a phase II trial.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous experiences we identified a novel schedule in which we use lower doses of carboplatin and gemcitabine in respect with those reported in the most part of the schedules of literature, whose activity and safety seemed to be comparable with those of literature [6][7][8]. In the actual experience, we hypothesize a novel role of our lowdoses schedule for the treatment of elderly patients with advanced NSCLC.…”
Section: Figurementioning
confidence: 81%
“…In this subgroup of patients, the carboplatin-containing doublet is an independent prognostic factor that improves overall survival. The schedule, that we showed to be active and effective in adult patients [6][7][8], seems to maintain its efficacy even in elderly patients with NSCLC, without worsening its safety profile. Nevertheless, further trials are probably needed to definitively validate this novel schedule in the treatment of fit elderly patients with advanced NSCLC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation